Optimal placement of DG in a Distributed Generation Environment (International Journal of Engineering and Computer Science, 2015)
The paper proposes optimal placement of fuel cells  and sizing of Distributed Generators (DG) in distribution networks are determined using optimization. The objective is to improve the reliability indices. The placement and size of DGs are optimized using a Genetic Algorithm (GA). To evaluate the proposed algorithm, the IEEE 34 buses distribution feeder,is used. And it also proposes new methodology using Particle Swarm Optimization approach (PSO) for the placement of Distributed Generators (DG) in the radial distribution systems to reduce the real power losses and to improve the system reliability. A hybrid objective function is used for the optimal DG placement. It has two parts, in first part the power loss purpose as one index named Power Loss Reduction Index is considered .in second part the effect of DG on reliability improvement of system is  considered and it is considered as one index named as Reliability Improvement Index. The proposed method is tested on standard IEEE 12 bus test system and the results are presented and compared with different approaches available in the literature. The proposed method has outperformed the other methods in terms of the quality of solution and computational efficiency.